PSYCHOLOGICAL ASPECT OF HERMENEUTICS - Tadjibayev, Musajon (Журнал иностранных языков и лингвистики, 2023)
The article aims to define new parameters of psychological hermeneutics in Uzbek literature. It illuminates the aspects of understanding a work of art that reveal the possibilities of artistic thinking.